Management challenges of spontaneous settlements in Ho Chi Minh City, Vietnam: A case study at Thoi Tam Thon county - Cong Tri, Hoang; Thien Phuoc, Pham Minh; Thanh Hung, Nguyen (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Informal housing is an acute phenomenon in most of the megacities of the developing countries. With the fast pace of urbanization, Ho Chi Minh City (HCMC) is facing rampant development of unorthodox houses. However, HCMC has some distinct differences to other cities in the developing countries: (I) Living environment of informal sectors is better, and (II) most households are able to legalize their houses. This is the results of flexible policies, in which local governments often legalized the ownerships and regularly upgraded infrastructures and facilities in informal areas. Although local government has attempted to reduce the number of informal housing, transactions in informal housing have been steadily increased in the last few years. Thoi Tam Thon County (TTTC), gathering a large number of illegally constructed houses in Hoc Mon District, HCMC, was selected as a pilot study to demonstrate the above differences and analyze policy challenges for informal housing. The survey showed that the costs of houses in the informal sectors are more affordable for low-income people. Additionally, living conditions in the impoverished neighborhoods are still acceptable. Results also reflect the awareness of the risks in illegally constructing houses. However, the affordable land prices and the opportunities to be legitimized are two major reasons encouraging low-income people take high risks. From the work presented in this paper, a few recommendations have been made to the local governments in order to have appropriate strategies to sustain urban growth and reduce informal housing in HCMC.Received: 15th March 2016; Revised: 25 th  October 2016; Accepted: 27th October 2016